Fraxin Promotes the Activation of Nrf2/ARE Pathway via Increasing the Expression of Connexin43 to Ameliorate Diabetic Renal Fibrosis - Chen, Rui; Zeng, Jingran; Li, Chuting; Xiao, Haiming; Li, Shanshan; Lin, Zeyuan; Huang, Kaipeng; Shen, Juan; Huang, Heqing (Frontiers in Pharmacology, 2022)
Diabetic nephropathy (DN) is quickly becoming the largest cause of end-stage renal disease (ESRD) in diabetic patients, as well as a major source of morbidity and mortality. Our previous studies indicated that the activation of Nrf2/ARE pathway via Connexin43 (Cx43) considerably contribute to the prevention of oxidative stress in the procession of DN. Fraxin (Fr), the main active glycoside of Fraxinus rhynchophylla Hance, has been demonstrated to possess many potential pharmacological activities. Whereas, whether Fr could alleviate renal fibrosis through regulating Cx43 and consequently facilitating the activation of Nrf2/ARE pathway needs further investigation. The in vitro results showed that: 1) Fr increased the expression of antioxidant enzymes including SOD1 and HO-1 to inhibit high glucose (HG)-induced fibronectin (FN) and inflammatory cell adhesion molecule (ICAM-1) overexpression; 2) Fr exerted antioxidant effect through activating the Nrf2/ARE pathway; 3) Fr significantly up-regulated the expression of Cx43 in HG-induced glomerular mesangial cells (GMCs), while the knock down of Cx43 largely impaired the activation of Nrf2/ARE pathway induced by Fr; 4) Fr promoted the activation of Nrf2/ARE pathway via regulating the interaction between Cx43 and AKT. Moreover, in accordance with the results in vitro, elevated levels of Cx43, phosphorylated-AKT, Nrf2 and downstream antioxidant enzymes related to Nrf2 were observed in the kidneys of Fr-treated group compared with model group. Importantly, Fr significantly improved renal dysfunction pathological changes of renal fibrosis in diabetic db/db mice. Collectively, Fr could increase the Cx43-AKT-Nrf2/ARE pathway activation to postpone the diabetic renal fibrosis and the up-regulation of Cx43 is probably a novel mechanism in this process.